Penilaian Kapasitas Masyarakat Dalam Menghadapi Bencana Banjir di Kecamatan Tapa, Kabupaten Bone Bolango, Provinsi Gorontalo - Rasna Wati; Koem, Syahrizal; Maryati, Sri (Jurnal Konservasi dan Rekayasa Lingkungan, 2024)
Flood is one of the most common hydrometeorological disasters in Indonesia. Indonesia as an area located on the Equator has the potential for extreme climates in the form of long droughts and high rainfall which can cause flood disasters. Given that floods are the most frequent disaster in Indonesia, community preparedness and capacity in dealing with flood disasters are needed in flood disaster management. Assessment of community and regional capacity in flood disaster management is very important to see the success in flood disaster risk reduction. The purpose of this study was to determine community preparedness for flood disasters in Tapa Sub-district, Bone Bolango Regency. This research used a survey method with data collection techniques through field observations, questionnaires, and interviews. The research data were analyzed by descriptive quantitative. The results showed that Talulobutu Village as a disaster response village is a village with a high community capacity preparedness index and regional resilience at level 5. The level of multi-disaster index preparedness in the research area varies from low to high which shows the level of preparedness to handle disasters.